4(3x-12)=12x(x-12)

Simple and best practice solution for 4(3x-12)=12x(x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-12)=12x(x-12) equation:



4(3x-12)=12x(x-12)
We move all terms to the left:
4(3x-12)-(12x(x-12))=0
We multiply parentheses
12x-(12x(x-12))-48=0
We calculate terms in parentheses: -(12x(x-12)), so:
12x(x-12)
We multiply parentheses
12x^2-144x
Back to the equation:
-(12x^2-144x)
We get rid of parentheses
-12x^2+12x+144x-48=0
We add all the numbers together, and all the variables
-12x^2+156x-48=0
a = -12; b = 156; c = -48;
Δ = b2-4ac
Δ = 1562-4·(-12)·(-48)
Δ = 22032
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{22032}=\sqrt{1296*17}=\sqrt{1296}*\sqrt{17}=36\sqrt{17}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(156)-36\sqrt{17}}{2*-12}=\frac{-156-36\sqrt{17}}{-24} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(156)+36\sqrt{17}}{2*-12}=\frac{-156+36\sqrt{17}}{-24} $

See similar equations:

| 24+6k=6(4-6k) | | g-0.16g=21 | | -6(2a-5)=126 | | 2x^2-x^2-15x=0 | | 20=9r-7 | | 7x-5x-16=-5x+5x | | 8+(n/3)=-2 | | -6+7r=2+6r | | 5x+2-10=4x-2+9x | | 17=a/5-2 | | 3(3n-6)=2(5n-2) | | (4z-46)=66 | | 1/9y+1/4=5/18 | | 3v+30=6(5+8v)-7v | | 4x+0.2=8.2 | | 21-6b=-3(5b-1) | | 14+2n+3n=3n+6 | | 12x^2-344x+1849=0 | | 2.1x+1.3×-4.6=22 | | -11-7a=1-5a | | -6(x-2)=1 | | -67r=2+6r | | 2=5(-7x+8)+3(x-2) | | 2x-1-3x/10+3/2=2(x-3)+1/5 | | 6(5-v8)+12=-54 | | -15=-3r-2r | | x/3+x/6+1=3x/2-1/2 | | 10800=x | | 4-(x-5)=8x-3(2x+3) | | 3x-2+1/2+x=21-2-x | | 10-x=3/2x | | 12-x/5=7 |

Equations solver categories